Artificial intelligence awareness and readiness among undergraduate students in Kwara State universities Nigeria - Afeez Abiola Hamzat; Seth Dade Ansah (UIN Raden Mas Said Surakarta, 2025)
The Fourth Industrial Revolution, driven by Artificial Intelligence (AI), is profoundly reshaping global landscapes, particularly education. This study investigated the awareness and readiness levels of undergraduate students regarding AI for learning within Kwara State universities, Nigeria, a region critically under-researched in this evolving discourse. Employing a quantitative survey research design, data were collected from 300 undergraduate students across selected private and government-owned universities using a questionnaire with a 4-point Likert scale. Mean scores determined awareness and readiness levels, while independent samples t-tests analyzed differences based on gender and university ownership. Key findings revealed a high overall level of AI awareness (Grand Mean = 2.71) and a high level of readiness to use AI for learning (Grand Mean = 2.66) among the students. Notably, the study found no statistically significant difference in AI awareness between male and female students (t = -0.82, p = 0.35). Similarly, there was no significant difference in AI readiness between students from private-owned and government-owned universities (t = -0.63, p = 0.27). These findings suggest a promising foundation for AI integration in Nigerian higher education, indicating that students are largely aware and prepared to embrace AI tools. The study contributes empirically to the limited literature on AI in education within Sub-Saharan Africa, offering valuable insights for policymakers and educators to strategically advance AI integration and foster a future-ready generation of graduates.